Hermit crabs (Decapoda: Crustacea) from deep Mauritanian waters (NW Africa) with the description of a new species - de Matos-Pita, Susana S.; Ramil, Fran (Zootaxa, 2015)
Thirteen hermit crab species of the families Diogenidae, Paguridae and Parapaguridae were captured in deep waters off Mauritania during Maurit surveys. A new species of the genus Paguristes, Paguristes candelae n. sp., is described. Areopaguristes mauritanicus n. comb. is proposed for Paguristes mauritanicus Bouvier, 1906 and Pseudopaguristes marocanus n. comb. for Paguristes marocanus A. Milne-Edwards & Bouvier, 1892; the females of the latter species are reported for the first time. Our data extends the geographical distribution of Pseudopaguristes marocanus southwards and that of Paragiopagurus macroceros northwards. Both species, together with Diogenes pugilator (Roux, 1829), are recorded for the first time in Mauritanian waters. New data about bathymetric ranges are also reported for Pseudopaguristes marocanus n. comb., Areopaguristes mauritanicus n. comb. and Paragiopagurus macroceros.